Design of a Recombinant Multivalent Epitope Vaccine Based on SARS-CoV-2 and Its Variants in Immunoinformatics Approaches - Yu, Mingkai; Zhu, Yuejie; Li, Yujiao; Chen, Zhiqiang; Li, Zhiwei; Wang, Jing; Li, Zheng; Zhang, Fengbo; Ding, Jianbing (Frontiers in Immunology, 2022)
The development of an effective multivalent vaccine against SARA-CoV-2 variants is an important means to improve the global public health situation caused by COVID-19. In this study, we identified the antigen epitopes of the main global epidemic SARS-CoV-2 and mutated virus strains using immunoinformatics approach, and screened out 8 cytotoxic T lymphocyte epitopes (CTLEs), 17 helper T lymphocyte epitopes (HTLEs), 9 linear B-cell epitopes and 4 conformational B-cell epitopes. The global population coverage of CTLEs and HTLEs was 93.16% and 99.9% respectively. These epitopes were spliced together by corresponding linkers and recombined into multivalent vaccine. In silico tests, the vaccine protein was a non-allergen and the docking with TLR-3 molecule showed a strong interaction. The immunogenicity of the vaccine was confirmed in vivo and in vitro finally. Therefore, our vaccine may have potential protection for SARA-CoV-2 and its variants.